2015
DOI: 10.4187/respcare.03671
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ambient Music on Perceived Exertion During a Pulmonary Rehabilitation Session: A Randomized Crossover Study

Abstract: BACKGROUND: Pulmonary rehabilitation is a key element in the treatment of COPD. Music has been shown to have a positive effect on parameters related to a decrease in exercise tolerance. The aim of this study was to evaluate the effect of listening to ambient music on perceived exertion during a pulmonary rehabilitation session for COPD subjects. METHODS: COPD subjects randomly performed a session of pulmonary rehabilitation with or without ambient music. Perceived exertion (Borg scales), anxiety (Hospital Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…Prior theory and research have begun to focus on the role of specific music features (rather than genres or styles) for individuals and groups (Greenberg et al, 2015(Greenberg et al, , 2016. Our findings in this pilot build on prior research that has shown that relaxing and ambient sounds and environments improve stress and anxiety in various clinical and medical contexts, including rehabilitation, pediatrics, soldiers suffering from posttraumatic stress, and in hospitals during preand post-operative settings (Calcaterra et al, 2014;Difede & Hoffman, 2002;George et al, 2007;Gromala et al, 2015; Hartling et al, 2013;Johnson et al, 2012;Knight & Rickard, 2001;Nilsson, 2009;Piskorz & Czub, 2018;Plante et al, 2006;Reychler et al, 2015;Rothbaum et al, 2001;Taneja et al, 2017;Tarrant et al, 2018;Thoma et al, 2013). Our findings also extend prior research which shows that low arousal and high depth music features can decrease perception of pain in experimental tasks (Basinski et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Prior theory and research have begun to focus on the role of specific music features (rather than genres or styles) for individuals and groups (Greenberg et al, 2015(Greenberg et al, , 2016. Our findings in this pilot build on prior research that has shown that relaxing and ambient sounds and environments improve stress and anxiety in various clinical and medical contexts, including rehabilitation, pediatrics, soldiers suffering from posttraumatic stress, and in hospitals during preand post-operative settings (Calcaterra et al, 2014;Difede & Hoffman, 2002;George et al, 2007;Gromala et al, 2015; Hartling et al, 2013;Johnson et al, 2012;Knight & Rickard, 2001;Nilsson, 2009;Piskorz & Czub, 2018;Plante et al, 2006;Reychler et al, 2015;Rothbaum et al, 2001;Taneja et al, 2017;Tarrant et al, 2018;Thoma et al, 2013). Our findings also extend prior research which shows that low arousal and high depth music features can decrease perception of pain in experimental tasks (Basinski et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…However, the college-aged, highly active participants who were tested in the Hutchinson et al study (13) are not comparable to the current sample of older outpatients with type 2 diabetes. Thus, although external stimuli do appear to capture attention during exercise in a clinical setting, they do not appear to influence RPE in this particular population (25).…”
Section: Perceptual Variablesmentioning
confidence: 76%
“…In another area, ambient music added to a standard PR session for patients with advanced COPD was observed to have positive effect, with a reduction of anxiety that was noticed after one session [60]. Despite a small sample size, this finding appears promising.…”
Section: Resultsmentioning
confidence: 99%